Diradical character and nonlinear optical properties of buckyferrocenes: focusing on the use of suitably modified fullerene fragments1. Issue 8 (28th February 2015) - Muhammad, Shabbir; Ito, Soichi; Nakano, Masayoshi; Kishi, Ryohei; Yoneda, Kyohei; Kitagawa, Yasutaka; Shkir, Mohd; Irfan, Ahmad; Chaudhry, Aijaz R.; AlFaify, Salem; Kalam, Abul; Al-Sehemi, Abdullah G.
<x xml:space="preserve">Abstract</x> Buckyferrocenes, made up of suitably modified fullerenes fragments having an uninterrupted π-electron network, show intermediate diradical character and robustly large third-order nonlinear optical responses.